Literarische Beziehungen zum Mittelalter - Becker, Ann-Marie (De Gruyter, 2025)
This study examines the question of when and how German-language texts written between 1750 and 1930 refer to the literature of the Middle Ages. In a scalable reading, it performs a distant reading of medieval references in German-language literature, followed by an examination of the reception of medieval poetry. It then carries out a close reading of Friedrich Haug’s Minnesang reception